A randomized controlled trial on Stroke telerehabilitation: The effects on falls self-efficacy and satisfaction with care. (April 2015) - Chumbler, Neale R; Li, Xinli; Quigley, Patricia; Morey, Miriam C; Rose, Dorian; Griffiths, Patricia; Sanford, Jon; Hoenig, Helen
Summary: We determined the effect of a multifaceted stroke telerehabilitation (STeleR) intervention on falls-related self-efficacy and satisfaction with care. We conducted a prospective, randomized, multisite, single-blinded trial in 52 veterans from three Veterans Affairs Medical Centers. Participants who experienced a stroke in the past 24 months were randomized to the STeleR intervention or usual care. Participants in the intervention arm were administered an exit interview to gather specific patient satisfaction data three months after their final outcome measure. The STeleR intervention consisted of three home visits, five telephone calls, and an in-home messaging device provided over three months to instruct patients in functionally based exercises and adaptive strategies. The outcome measures included Falls Efficacy Scale to measure fall-related self-efficacy and a Stroke-Specific Patient Satisfaction with Care (SSPSC) scale, a measure separated into two subscales (satisfaction with home care and satisfaction with hospital care) was employed to measure the participants' satisfaction. At six months, compared with the usual care group, the STeleR group showed statistically significant improvements in one of the two SSPSC scales (satisfaction with hospital care, p = .029) and approached significance in the second SSPSC scale (satisfaction with home care, p = .077). There were no improvements in fall-related self-efficacy. Core concepts identified were: (a) beneficial impact of the trained assistant; (b) exercises helpful; (c) home use of technology. The STeleR intervention improved satisfaction with care, especially as it relates to care following their experience from the hospital. With the limited resources available for in-home rehabilitation for stroke survivors, STeleR (and especially its exercise components) can be a useful complement to traditional post-stroke rehabilitation.